Leksikal Bahasa Minangkabau Penutur Tua dan Penutur Muda di Nagari Pangkalan, Kecamatan Pangkalan Koto Baru - Damelza, Dwika Pavina; Nadra, Nadra; Reniwati, Reniwati (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This study explores the assumption that Pangkalan, situated as a transit area between West Sumatra and Riau, experiences considerable linguistic interaction, potentially leading to lexical variations in the Minangkabau language. The research focuses on identifying and describing lexical differences in the Minangkabau language as used by both older and younger speakers, further distinguishing between those with formal schooling and those without. Data were gathered through observation and elicitation methods, employing a descriptive qualitative approach to capture lexical variations among speakers in Nagari Pangkalan. Analysis involved both referential and translational equivalent methods. Out of 744 lexical concepts analyzed, 216 exhibited variations between older and younger speakers. Additionally, 23 unique lexical differences were noted among young speakers based on their educational background. Notably, 45 lexical items were distinctive to older speakers, whereas 10 were unique to younger speakers. Contrary to the initial hypothesis that Pangkalan's role as a transit area would heavily influence lexical variation, the study found that educational factors played a more significant role in shaping the observed lexical differences.